تطبيق المدخل الاتصالي Communicative Approach)) في تعليم المحادثة لطلبة الفصل الحادي عشر - Fila Intana Zahro Annisa (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Language studying approach that emphasizes domination of language skills more than language structure well known by the communicative approach. Purpose of this research is to describe the application of a communicative approach in Arabic learning to improve muhadatsah competence. This method chosen to be used in this research is sighting and interviewing method of whose data comes from various sources involved to this study research. The great output of this study represent that the communicative approach emphasizes listening and speaking skills. Objectivity of learning to be achieved through these various sources are to be connected to communicate with the second language being studied anytime and anywhere, which is in approval with the nature of language studying